Biologic Treatment in Elderly Patients with Psoriasis: Focus on Safety and Adherence - Pehlivan Ulutaş, Gizem; Özkök Akbulut, Tuğba (Dermatology Practical & Conceptual, 2026)
Introduction: The number of elderly psoriasis patients is increasing, yet data on biological treatments in this population remains limited. Objectives: To evaluate the characteristics, efficacy, and safety of biologics in psoriasis patients aged ≥65 years and identify factors contributing to treatment interruption or discontinuation. Methods: The study included psoriasis patients aged ≥65 years who had received at least one biological treatment at a tertiary center for a minimum of 24 weeks between 2022 and 2024. Demographic and clinical data, treatment history, PASI scores, adverse events, and reasons for treatment interruption or discontinuation were evaluated. Results: Among 231 patients on biologics, 43 (18.6%) were aged ≥65 years (mean age: 70.2 ± 4.8 years, male-to-female ratio: 2:1). Mean PASI scores improved from 14.5 ± 8.8 at baseline to 1.5 ± 1.5 at weeks 12–16, and to 0.83 ± 1.2 at week 52. Latent tuberculosis and anti-HBc positivity were common (65.1% and 51.2%, respectively), but no reactivation occurred. Adverse events were reported in 39.5% of patients, most commonly infections (27.9%). Treatment-ending events occurred in 7.0%, all due to malignancies. Treatment interruptions occurred in 20.9%, mainly due to noncompliance, transportation difficulties, and comorbidities. Notably, 20.9% of the patients required assistance to attend their hospital visits, and 44.2% required help administering their drug. Treatment was discontinued in 16.3%, primarily due to malignancies and secondary failure. Conclusions: Biologics are effective in psoriasis patients aged ≥65 years. A relatively high malignancy rate emphasizes the importance of age-appropriate screening. Noncompliance, comorbidities, transportation problems, and healthcare access barriers may pose challenges in long-term treatment maintenance.